2019
DOI: 10.1111/inr.12505
|View full text |Cite
|
Sign up to set email alerts
|

Traditional methods for managing illness in newborns and infants in an Arab society

Abstract: Aim This study explored self‐management practices in relation to traditional methods for managing illness in newborns and infants and the implications of these practices on infant health. Background Self‐medication with folk remedies is believed to have short‐ and long‐term impacts on well‐being. Little is known about how mothers in Arab societies used their traditional beliefs and practices in self‐managing their newborns’ and infants’ health. Methods Data were collected from five focus groups using open‐ende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In contrast another study in Jordan [35] and Arab society [36] which showed that neonatal care in mothers most lacked knowledge.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast another study in Jordan [35] and Arab society [36] which showed that neonatal care in mothers most lacked knowledge.…”
Section: Discussionmentioning
confidence: 81%
“…10 In a country like Jordan where family ties and cultural heritage are paramount and pervasive, health beliefs may influence health outcomes or may produce certain traditional practices that may shape self-management of illnesses. 2 There is increasing recognition that families are often involved in decision-making during illness; however, little is known about how health beliefs influence decisions or behaviours related to managing an illness in the Arab world. Such knowledge will enable successful translation of culturally specific programs targeting health promotion and self-management of illness in Arab societies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a person interested in folk remedies may use a complex system of traditional remedies mostly based on psychosocial interventions, mild herbs, ritualistic behaviour or household items. 2 , 3 The use of folk remedies to manage illness is often influenced by family beliefs and the natural or social environment they live in. 4 , 5 In this instance, understanding the relationship between health beliefs and traditional practices is important in conceptualising the capacity of families to manage illness during acute or chronic illness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations